Early relapse after high‐dose melphalan autologous stem cell transplant predicts inferior survival and is associated with high disease burden and genetically high‐risk disease in multiple myeloma. (10th June 2020) - Bygrave, Ceri; Pawlyn, Charlotte; Davies, Faith; Craig, Zoe; Cairns, David; Hockaday, Anna; Jenner, Matthew; Cook, Gordon; Drayson, Mark; Owen, Roger; Gregory, Walter; Morgan, Gareth; et al.
Summary: Predicting patient outcome in multiple myeloma remains challenging despite the availability of standard prognostic biomarkers. We investigated outcome for patients relapsing early from intensive therapy on NCRI Myeloma XI. Relapse within 12 months of autologous stem cell transplant was associated with markedly worse median progression‐free survival 2 (PFS2) of 18 months and overall survival (OS) of 26 months, compared to median PFS2 of 85 months and OS of 91 months for later relapsing patients despite equal access to and use of subsequent therapies, highlighting the urgent need for improved outcome prediction and early intervention strategies for myeloma patients.